Impact of Destination Image and Quality Service on Tourist Satisfaction and Loyalty at Malalayang Beachwalk, Manado, North Sulawesi - Emmanuella Felice’anna Dije Karisoh; I Wayan Suardana; I Gusti Putu Bagus Sasrawan Mananda (International journal of technology and education research, 2024)
Tourism is a key sector in Indonesia’s economy, contributing up to USD 20 billion annually. With its diverse natural landscapes and cultural heritage, Indonesia has prioritized five key tourism destinations, including North Sulawesi. Malalayang Beachwalk, which opened in October 2022, features impressive views and attractions but has faced complaints about its facilities and services, such as unwelcoming vendor behavior and high parking fees, which have impacted tourist satisfaction. This study aims to examine how the destination image and service quality affect tourist satisfaction and loyalty at Malalayang Beachwalk. Utilizing a quantitative explanatory approach and SmartPLS 3.0 for analysis, the research surveyed 100 domestic tourists who visited between October 2022 and May 2024. The findings demonstrate that both the destination image and service quality significantly and positively influence tourist satisfaction and loyalty. Additionally, tourist satisfaction has a notable impact on loyalty. These results suggest that improving both the destination image and service quality at Malalayang Beachwalk can boost tourist satisfaction and loyalty, leading to more repeat visits. The study provides valuable insights for management to address current issues and better meet tourist expectations, thereby supporting the successful growth of the tourism destination.